Restorative Justice sebagai Sanksi Pemidanaan dalam Tindak Pidana Narkotika di Indonesia - Putra, Ivan Erranza; Hartiwiningsih, Hartiwiningsih; Zulfiani, Anita (Indonesian Publication Center, 2026)
Drug abuse constitutes a form of criminal offense with distinct and complex characteristics, as in many cases the perpetrators are not merely offenders but also individuals suffering from dependence on addictive substances. This condition places drug abusers in a dilemmatic position, since on the one hand they violate criminal law provisions, while on the other hand they require special treatment in the form of recovery and care. Therefore, the application of conventional punitive approaches that emphasize imprisonment is often considered insufficient to comprehensively address drug-related problems. Such approaches may even generate further issues, including prison overcrowding, the failure to achieve rehabilitation objectives, and the low effectiveness of behavioral reform among offenders. In this context, an alternative approach that prioritizes humanitarian values, recovery, and social benefit is required, one of which is the application of the restorative justice concept. This approach emphasizes the restoration of the offender’s condition without disregarding the interests of society and the state. This research aims to examine and analyze the concept of restorative justice in the handling of drug-related criminal offenses, to review its legal regulation within the Indonesian positive legal system, and to assess its relevance in light of fundamental principles of criminal law, particularly justice, utility, legal certainty, and criminal liability. The research employs a normative legal research method using statutory and conceptual approaches, conducted through library research on primary, secondary, and tertiary legal materials related to drug offenses and restorative justice. The findings indicate that the application of restorative justice in drug-related crimes may be implemented in a limited and selective manner, particularly for offenders classified as drug abusers or addicts who are not involved in illicit drug trafficking networks. This approach prioritizes medical and social rehabilitation as forms of recovery, thereby offering a more balanced, just, and effective alternative to conventional punishment.